Risk Factors Associated With Lower Bone Mineral Density in Primary Aldosteronism Patients - Lv, Xiaomei; Hu, Huijun; Shen, Chuyu; Zhang, Xiaoyun; Yan, Li; Zhang, Shaoling; Guo, Ying (Frontiers in Endocrinology, 2022)
Purpose: The association between primary aldosteronism (PA) and lower bone mass density (BMD) has raised concern, but the contributing factors remains unclear. We aim to explore risk factors for lower BMD in PA patients. Methods: We analyzed and compared data of 60 PA patients with 60 matched EH patients. BMD, bone metabolites and several oxidative stress and inflammation indicators including C-reactive protein (CRP), superoxide dismutase (SOD), total bilirubin (TBIL), mean platelet volume (MPV) et al. were assessed and compared in PA and essential hypertension (EH) patients. Bivariate correlation analysis and multivariate linear regression analysis were performed to explore factors associated with BMD in PA patients. Results: BMD measured by quantitative computed tomography in PA patients was lower than that in EH patients (140.9±33.0 vs. 159.6±43.2 g/cm3, p=0.047), especially in patients less than 50 years old. BMD was independently negatively associated age (standardized β=-0.581, p<0.001), serum phosphorus (standardized β=-0.203, p=0.008), urinary calcium excretion (standardized β=-0.185, p=0.031), MPV (standardized β=-0.172, p=0.043), and positively associated with SOD (standardized β=0.205, p=0.011) and TBIL (standardized β=0.212, p=0.015). Conclusions: PA patients showed lower BMD than EH patients, which was associated with age, serum phosphorus, urinary calcium excretion, MPV, SOD and TBIL. These variables might be potential markers for assessment of bone loss and efficacy of treatments in PA patients.